Room-temperature InP distributed feedback laser array directly grown on silicon - Wang, Zhechao; Tian, Bin; Pantouvaki, Marianna; Guo, Weiming; Absil, Philippe; Van Campenhout, Joris; Merckling, Clement; Van Thourhout, Dries (Nature photonics, 2015)
Fully exploiting the silicon photonics platform for large-volume, cost-sensitive applications requires a fundamentally new approach to directly integrate high-performance laser sources using wafer-scale fabrication methods. Direct-bandgap III–V semiconductors allow efficient light generation, but the large mismatch in lattice constant, thermal expansion and crystal polarity makes their epitaxial growth directly on silicon extremely complex. Using a selective-area growth technique in confined regions, we surpass this fundamental limit and demonstrate an optically pumped InP-based distributed feedback laser array monolithically grown on (001)-silicon operating at room temperature and suitable for wavelength-division-multiplexing applications. The novel epitaxial technology suppresses threading dislocations and anti-phase boundaries to a less than 20-nm-thick layer, which does not affect device performance. Using an in-plane laser cavity defined using standard top-down lithographic patterning together with a high yield and high uniformity provides scalability and a straightforward path towards cost-effective co-integration with silicon photonic and electronic circuits. Scientists demonstrate an optically pumped InP-based distributed feedback laser array monolithically grown on (001)-silicon operating at room temperature that is suitable for wavelength-division multiplexing applications.